Negócios jurídicos processuais no modelo constitucional do processo civil e a atuação do estado-juiz na fase de instrução - Sá, Rodolfo Seabra Alvim Bustamante (2022)
This article aims to present one of the main innovations of the 2015 Code of Civil Procedure, and, consequently, a novelty introduced in Brazilian law. The validity and existence requirements of the typical and atypical procedural deals will be presented, the constitutionally foreseen limits, as well as the legitimacy and performance of the judge to control the validity and effectiveness of the procedural legal deals